Green corrosion inhibitors: amino acids and plant extracts - Elphick, D.; Ajayi, O.; Everitt, N.M.; Voisey, K.T. (2015)
Corrosion inhibitors are chemicals that are used in many industries to control corro-sion. As they are injected into process streams they have to be continually replen-ished in order to maintain protection. Many chemicals used are environmentally un-friendly highly toxic compounds including chromates and arsenic compounds. REACH legislation and PARCOM recommendations as well as general environmen-tal concerns are driving an effort to find acceptable alternatives to conventional cor-rosion inhibitors. Promising initial work in the open literature has already identified several alternative green corrosion inhibitors, including plant extracts that have po-tential to be used as more environmentally acceptable corrosion inhibitors. However, to date a lot of the work has been done on a trial and error basis with little considera-tion of the mechanisms of inhibition or any detailed characterisation of the inhibited surface. Three candidate types of environmentally friendly corrosion inhibitors are identified as worth of further consideration: the amino acids histidine and tryptophan, aloe vera plant extract and plants with high inulin contents. Initial results on the effectiveness of the amino acids in protecting mild steel in an acidic environment are determined via immersion tests and weight loss measurements. The evolution of the inhibition film is studied using electrochemical measurements. Experiments are carried out at tem-peratures of 20 ⁰C to 60 ⁰C. Results are compared with those from the widely used corrosion inhibitor propargyl alcohol. The amino acids show some effectiveness as corrosion inhibitors in the environment used however further work on other candidate green corrosion inhibitors, including full lifecycle costing, is required to fully assess their potential. 1 Introduction